2008
DOI: 10.1142/s0129626408003351
|View full text |Cite
|
Sign up to set email alerts
|

A Gentle Introduction to S-Net: Typed Stream Processing and Declarative Coordination of Asynchronous Components

Abstract: We present the design of S-NET, a coordination language and component technology based on stream processing. S-NET achieves a near-complete separation between application code, written in a conventional programming language, and coordination code, written in S-NET itself. S-NET boxes integrate existing sequential code as stream-processing components into streaming networks, whose construction is based on algebraic formulae built out of four network combinators. Subtyping on the level of boxes and networks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…As our benchmark, we chose a fast fourier transform (FFT), face detection (FD), and data encryption standard (DES) applications implemented using the S-Net [22] streaming language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As our benchmark, we chose a fast fourier transform (FFT), face detection (FD), and data encryption standard (DES) applications implemented using the S-Net [22] streaming language.…”
Section: Methodsmentioning
confidence: 99%
“…Nodes can be connected in different patterns, such as pipelines and parallel networks. Some examples of stream programming can be found in [21][22][23].…”
Section: Stream Programmingmentioning
confidence: 99%
“…The first comprehensive solution for S-Net was by Grelck and Shafarenko (see [20], where the language definition and some relevant algorithms are presented). Further development of the type system was done by Cai et al [21] and some recent examples of the use of S-Net in applications are found in [18].…”
Section: Related Workmentioning
confidence: 99%
“…To support the parallel component technology being discussed, a coordination language has been designed and implemented [20,18]. The language is called S-Net, which stands for Streaming Networks.…”
Section: Languagementioning
confidence: 99%
“…Examples of systems that use the streaming approach include Auto-Pipe [6], [11], S-Net [14], Streams-C [12], and StreamIt [29]. In the streaming paradigm, an application is decomposed into processing kernels, or blocks, which are connected using explicit communication channels.…”
Section: Introductionmentioning
confidence: 99%